﻿Notulae to the Italian native vascular flora: 12 - Fabrizio Bartolucci (Pensoft Publishers, 2021)
In this contribution, new data concerning the distribution of native vascular flora in Italy are presented. It includes new records, confirmations, exclusions, and status changes to the Italian administrative regions. Nomenclatural and distribution updates, published elsewhere, and corrigenda are provided as Suppl. material 1.